Предмет: Математика,
автор: NastuaFil
решите уравнение -2=-9-2(-1х+1) заранее спасибо
Ответы
Автор ответа:
0
-2 = - 9 - 2(-1х + 1)
- 2 = - 9 - 2 * (-1х) - 2 *1
-2 = - 9 + 2х - 2
-2 = -11 +2х
2х - 11 = -2
2х = -2 +11
2х = 9
х = 9/2 = 4 1/2
х= 4,5
- 2 = - 9 - 2 (-1 *4,5 + 1)
- 2 = - 9 - 2 * (-3,5)
-2 = -9 +7
- 2 = -2
- 2 = - 9 - 2 * (-1х) - 2 *1
-2 = - 9 + 2х - 2
-2 = -11 +2х
2х - 11 = -2
2х = -2 +11
2х = 9
х = 9/2 = 4 1/2
х= 4,5
- 2 = - 9 - 2 (-1 *4,5 + 1)
- 2 = - 9 - 2 * (-3,5)
-2 = -9 +7
- 2 = -2
Автор ответа:
0
спасибки большое
Автор ответа:
0
всегда пожалуйста)
Похожие вопросы
Предмет: География,
автор: KseshaGaara
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: dadha98
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: Thanksfor